Knowing is Not Enough: Engaging in the Knowledge Economy - Bannerman, Valentina J.A. (Ghana Library Journal, 2012)
The paper focuses on the place of the library in the Knowledge Economy and the need for librarians to evolve alongside the changing needs of library patrons. It discusses Ghana's ranking in the Knowledge Economy Index and indicates that though the country has made considerable strides in ICT and Education, progress is not reflected in the status of most institutions. Also, the role of the library in the development of the country is not known by stakeholders. The paper discusses the role of the library in transition from information management to knowledge management to reflect the needs of the knowledge economy. It mentions efforts by some libraries that are using technology to assist users to access, create and share information as well as knowledge, through Library Automation, Open Access, Web 2.0 technologies and Information Literacy. It exhorts librarians to empower themselves so that they can become active participants and not passive observers in the transition of the country to the knowledge economy.